The interaction among multiple governance mechanisms in young newly public firms - Berry, Tammy K.; Paige Fields, L.; Wilkins, Michael S. (Journal of Corporate Finance, 2006)
We focus on the relations among inside ownership, board composition, unaffiliated block ownership, and compensation structure for a sample of firms following their IPOs. Specifically, we follow firms for up to eleven years after their IPOs and examine the full sample and subsamples of firms that survive, are acquired, or that file for bankruptcy during the sample period. We find that as CEO ownership declines, board independence, board seats held by venture capitalists, and unaffiliated block ownership increase. Our findings suggest that as inside ownership decreases alternative governance mechanisms evolve to help mitigate the resulting increase in agency costs. Interestingly, the associations between CEO ownership, the fraction of venture capital board membership, and unaffiliated block ownership exist only for firms that survive over the eleven-year sample period.